Noon- A Journal of Contemporary Art and Visual Culture : 3- Rethinking Truth, Information and Visual Art 2011 - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2011)
Contents: Dong-Jin Seo 'Preface: In between Information and truth', Jacques Ranciere 'Thinking Between Disciplines', Nam-See Kim 'The Truths and Untruths about the Visible', Sven Lutticken 'Suspense and Shock', Sumi Kang 'The Waeriness of Sensation', Sung-Huhn Lee 'Toward a Neo-Maichaeism, Pelin Tan 'Forms of Visibility: Distribution of Counter-Value', Thierry Raspail and Yongwoo Lee 'Biennales as Social Media', Joseph Grima 'Biennale Review- Gwangju Design Biennale 2011', Carol Yinghua Lu 'Orphans and Agents', Gwangju Biennale 2012.
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions